Localized Inlay Extended Tuberosity Block Bone Graft Technique: Simultaneous Management of Unfavorable Posterior Intermaxillary Space and Vertical Ridge Deficiency - Seied Omid Keyhan; Seifollah Hemmat; Sina Ghanean; Alireza Jahangirnia (Regeneration, Reconstruction & Restoration, 2016)
After extraction of posterior mandibular teeth, posterior dentoalveolar maxillary extrusion is a common finding in edentulous patients. As the edentulous area continues to atrophy, there is a continuous loss of bone height and density as well as antral pneumatization. Various techniques can be used for correction of this condition. The present article presents an innovative technique that can correct moderate to severe localized defects of the alveolar process prior to implant placement in the posterior maxillary ridge. The combination of extended tuberosity block bone graft harvesting with modified alveoloplasty (alveolectomy) and quadrilateral open sinus lift (localized inlay tuberosity block bone graft technique) is presented as an alternative to simple alveoloplasty for management of the deficient interarch space and antral pneumatization for prosthetics rehabilitation in the posterior edentulous maxillary segments. Surgical intrusion of the osteotomised bone segment as a corticocancellous block bone graft to the sinus cavity results in adequate interarch space and simultaneous vertical ridge augmentation in deficient posterior maxillary ridge for surgical and prosthetic outcomes without the need to harvest bone from another site. This quick and simple method does not need general anesthesia and has fewer complications. Localized inlay extended tuberosity block bone graft can be used as an alternative to simple alveoloplasty and posterior maxillary segmental osteotomy in distal extended edentulous patients for simultaneous management of unfavorable interocclusal distance and sinus pneumatization.